2023
DOI: 10.3390/laws12030049
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Participation in Care and Protection Decision-Making Matters

Judith Cashmore,
Peiling Kong,
Meredith McLaine

Abstract: Laws and policies in different jurisdictions provide a range of mechanisms that allow children involved in child protection processes and care proceedings to express their views when decisions that affect them are being made. Whether these mechanisms facilitate children’s involvement and whether they result in children’s views being heard and “given due weight in accordance with the age and maturity of the child”, as required by article 12 of the UN Convention on the Rights of the Child, is the focus of this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…Adolescents' participation in society is essential to ensure just treatment of this important social group (Patton et al 2016(Patton et al , 2018Sawyer et al 2012). As shown by many of the articles in this Special Issue, ensuring greater participation by children and adolescents is essential for best practice and good outcomes in a range of settings spanning child care and protection decision-making (Cashmore et al 2023); medical decision-making (Jowett et al 2022); and forensic interviewing in child sexual abuse investigations (Holder et al 2023). Enhanced participation also boosts civic engagement, and will enhance social policy, and ensure pressing social issues are more fully understood and can be remediated by appropriate social policy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Adolescents' participation in society is essential to ensure just treatment of this important social group (Patton et al 2016(Patton et al , 2018Sawyer et al 2012). As shown by many of the articles in this Special Issue, ensuring greater participation by children and adolescents is essential for best practice and good outcomes in a range of settings spanning child care and protection decision-making (Cashmore et al 2023); medical decision-making (Jowett et al 2022); and forensic interviewing in child sexual abuse investigations (Holder et al 2023). Enhanced participation also boosts civic engagement, and will enhance social policy, and ensure pressing social issues are more fully understood and can be remediated by appropriate social policy.…”
Section: Discussionmentioning
confidence: 99%
“…Legal and policy frameworks provide a range of mechanisms aiming to involve children who are the subject of child protection processes and care proceedings to express their views about decisions that affect them. Cashmore et al (2023) considered the extent to which these mechanisms facilitate children's involvement and whether they result in children's views being heard and given due weight in accordance with the child's age and maturity, as required by the UNCRC art 12. Through a review of existing work, and a novel analysis of law, policy and practice in New South Wales, Australia, Cashmore et al (2023) identified how children want to be involved in decisions which affect them.…”
Section: The Evolving Legal Landscapementioning
confidence: 99%
See 2 more Smart Citations
“…No matter their distance, parents must defend their children's hadhanah rights. [34] According to Article 14 of the Child Protection Law, a parent is responsible for a child's care, support, education, living expenses, and healthy growth and development when they divorce. These benefits will shape the child's character.…”
Section: Of 2014 Concerning Child Protectionmentioning
confidence: 99%